On the conversion of Indians and Heathens - D. Britz (Acta Theologica)
Read a review of Ineke Loots – Joke Spaans (eds.), Johannes Hoornbeeck (1617-1666), On the conversion of Indians and Heathens. An annotated translation of De conversione Indorum et gentilium (1669), [Brill’s Studies in Intellectual History 290/21], (Leiden – Boston: Brill, 2018), Johannes Hoornbeeck (1617- 1666), On the conversion of Indians and Heathens, ISBN: 978-90-04-25544-9, List price: Euro 129 / US$ 149.